Full tilt - Shusterman, Neal (Simon & Schuster BFYR, 2009)
When sixteen-year-old Blake goes to a mysterious, by-invitation-only carnival he somehow knows that it could save his comatose brother, but soon learns that much more is at stake if he fails to meet the challenge presented there by the beautiful Cassandra.